Nano-silicon environment-friendly water-based floor paint and preparation process thereof

By leveraging the synergistic effect of borate-urethane modified polysiloxane and bio-based polyol-polysiloxane block copolymer with nano-silica sol, the problems of insufficient environmental friendliness, poor weather resistance, weak wear resistance and low adhesion of water-based floor coatings have been solved, achieving a high-performance coating performance improvement.

CN120966347AActive Publication Date: 2025-11-18DALIAN YOUHUA CONSTR MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511267835.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-11-18
Estimated Expiration
2045-09-05

AI Technical Summary

Technical Problem

Existing water-based floor coatings suffer from insufficient environmental friendliness, poor weather resistance, weak abrasion resistance, low adhesion, and inadequate water resistance, making it difficult to meet the long-term use requirements of high-traffic floors.

Method used

By utilizing the synergistic effect of borate-urethane modified polysiloxane and bio-based polyol-polysiloxane block copolymer with nano-silica sol, the interfacial bonding force between nano-silica and resin is enhanced through the formation of Si-OB covalent bonds and dynamic hydrogen bonds, resulting in a dense structure and improving the hardness, flexibility and weather resistance of the coating.

Benefits of technology

It significantly improves the adhesion, abrasion resistance, and weather resistance of the coating, reduces the content of volatile organic compounds, meets high-standard usage requirements, and is suitable for ground protection in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005583781200000101
    Figure BDA0005583781200000101
Patent Text Reader

Abstract

The invention discloses a nano silicon environment-friendly water-based floor paint and a preparation process thereof in the technical field of environment-friendly coatings. The invention provides two brand-new modified compounds, namely boric acid ester-carbamate modified polysiloxane and a bio-based polyol-polysiloxane block copolymer. The interface bonding of the nano silicon and the resin is enhanced through a borate group, so that the water resistance and the adhesive force are improved; the latter utilizes the flexibility of the bio-based component and the weather resistance of polysiloxane to balance the hardness and impact resistance of the coating. The floor paint is prepared by taking water-borne epoxy resin as a film-forming main body, filling pores by combining with nano silica sol, assisting with auxiliaries such as a dispersing agent and a defoaming agent, and carrying out processes such as mixing, high-speed dispersion and viscosity regulation. The prepared product is excellent in environmental protection property, is remarkably improved in weather resistance, wear resistance, adhesive force and water resistance, and is suitable for scenes with relatively high performance requirements, such as industrial factory buildings and commercial grounds.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of environment-friendly coatings, in particular to a nano-silicon environment-friendly water-based floor paint and a preparation process thereof. BACKGROUND

[0002] Traditional floor coatings are mainly solvent-based products, which release a large amount of volatile organic compounds (VOC) during production and construction, posing a serious threat to air quality and human health. With increasingly stringent environmental regulations, water-based floor paint has gradually become the mainstream due to its low VOC and no solvent evaporation. However, the existing water-based floor paint still has significant technical bottlenecks: the hardness and wear resistance of the film are insufficient, making it difficult to meet the long-term use requirements of high traffic floors; the adhesion of the coating to the cement base is greatly affected by environmental humidity and temperature, and is prone to peeling; the weather resistance is poor, and it is easy to powder and discolor when exposed to ultraviolet light or humid environment for a long time; the function is single, and it is difficult to balance environmental protection and comprehensive performance improvement, which cannot meet the needs of high-standard scenarios such as industrial plants and commercial floors.

[0003] Nano-silicon material is considered as a key filler to improve the performance of water-based floor paint due to its small particle size, large specific surface area, and high surface energy. Its high hardness can enhance the wear resistance of the coating, and its small particle size can fill the pores of the coating to improve the density. However, the surface of nano-silicon has a large number of inert silicon hydroxyl groups, which are prone to agglomeration through hydrogen bonding, resulting in uneven dispersion. At the same time, the interfacial bonding between nano-silicon and the resin matrix is weak, making it difficult to exert the reinforcing effect of nano-particles. Traditional modification methods rely on single silane coupling agent or organosilicon monomer, which can only improve the dispersion of nano-silicon or the flexibility of the resin, and cannot solve the problems of weak interfacial bonding and insufficient comprehensive performance, limiting the efficient application of nano-silicon in water-based floor paint.

[0004] In view of the above problems, it is crucial to develop a new modified material that has good dispersion stability of nano-silicon, strong function of the resin matrix, and enhanced interfacial bonding. The existing modified compounds have single function, making it difficult to simultaneously improve adhesion, weather resistance, and wear resistance, and cannot meet the use requirements in complex environments. Therefore, it is urgent to design two new modified compounds to simultaneously improve the dispersion stability of nano-silicon and the performance of the resin matrix, and to realize the breakthrough of multiple properties such as strong interface, high toughness, and super weather resistance through synergistic effect, providing a new path for the research and development of high-performance environment-friendly water-based floor paint. SUMMARY

[0005] The present application relates to the technical field of environment-friendly coatings, in particular to a nano-silicon environment-friendly water-based floor paint and a preparation process thereof.

[0006] The present application achieves the above-mentioned purposes through the following technical solutions:

[0007] A nano-silicon environmentally friendly water-based floor coating comprises the following raw materials in parts by weight:

[0008] Waterborne epoxy resin: 200-300 parts by weight;

[0009] Boronate-urethane modified polysiloxane: 40-90 parts by weight;

[0010] Bio-based polyol-polysiloxane block copolymer: 60-120 parts by weight;

[0011] Nano silica sol: 200-300 parts by weight;

[0012] Deionized water: 150-250 parts by weight;

[0013] Dispersant: 7-12 parts by weight;

[0014] Defoamer: 4-6 parts by weight;

[0015] Thickener: 8-12 parts by weight;

[0016] Leveling agent: 3-5 parts by weight;

[0017] Titanium dioxide: 50-100 parts by weight;

[0018] Light stabilizer: 6-10 parts by weight;

[0019] The preparation method of the borate-urethane modified polysiloxane includes: A1, dissolving α,ω-dihydroxypolydimethylsiloxane in anhydrous xylene, adding 1,6-hexanediisocyanate, and reacting under nitrogen protection at 75-76℃; A2, subsequently adding polycaprolactone diol, and reacting at 55-56℃; finally adding boric acid, reacting at 90-92℃, distilling under reduced pressure, washing with acetone, and drying under vacuum.

[0020] In this invention, the two terminal hydroxyl groups (-OH) in the α,ω-dihydroxy polydimethylsiloxane molecule undergo a nucleophilic addition reaction with the isocyanate group (-NCO) of 1,6-hexamethylene diisocyanate. The carbon atom of the isocyanate group is electrophilic due to the electron-withdrawing effect of the nitrogen atom, and the oxygen atom of the hydroxyl group acts as a nucleophile, attacking this carbon atom to form a urethane bond (-NH-CO-O-), thereby introducing a polyurethane segment into the polysiloxane backbone. The subsequently added polycaprolactone diol contains multiple hydroxyl groups, and the hydroxyl groups on its molecular chain continue to undergo similar nucleophilic addition reactions with unreacted isocyanate groups, extending the length of the polyurethane segment and forming a preliminary "polysiloxane-polyurethane" block structure. Finally, the added boric acid contains three hydroxyl groups, which can undergo a condensation reaction with the remaining hydroxyl groups in the system (from the polycaprolactone diol or polysiloxane side chains), removing water molecules and forming a stable borate group. This group, through the strong interaction between the oxygen atom and the silanol (-Si-OH), significantly enhances the interfacial bonding between nano-silicon and the resin.

[0021] According to a preferred embodiment of the present invention, the waterborne epoxy resin is purchased from Wanhua Chemical Group Co., Ltd., and the model is E-51.

[0022] According to a preferred embodiment of the present invention, the α,ω-dihydroxypolydimethylsiloxane was purchased from Bluestar Organosilicon (Shanghai) Co., Ltd., and the model number is 202-100.

[0023] According to a preferred embodiment of the present invention, the xylene was purchased from Sinopec Shanghai Petrochemical Co., Ltd., and was industrial grade xylene (purity ≥99.5%).

[0024] According to a preferred embodiment of the present invention, the 1,6-hexamethylene diisocyanate was purchased from Wanhua Chemical Group Co., Ltd., and the product name is HDI-100.

[0025] According to a preferred embodiment of the present invention, the nitrogen gas is purchased from Yingde Gas Co., Ltd., and is industrial grade nitrogen gas (purity ≥99.99%).

[0026] According to a preferred embodiment of the present invention, the polycaprolactone diol was purchased from Zhejiang Hengxiang Chemical Co., Ltd., and the model number is PCL-1000.

[0027] According to a preferred embodiment of the present invention, the boric acid was purchased from Qinghai Salt Lake Industry Co., Ltd., and the type was industrial grade boric acid (H3BO3≥99.5%).

[0028] According to a preferred embodiment of the present invention, the acetone was purchased from Jiangsu Sanmu Group Co., Ltd., and the product was industrial grade acetone (purity ≥99.5%).

[0029] According to a preferred embodiment of the present invention, the nano-silica sol was purchased from Zhuzhou Xinglong New Materials Co., Ltd., and the model is XLS-40 (particle size 40±5nm).

[0030] According to a preferred embodiment of the present invention, the deionized water is purchased from Shanghai Canature Environmental Protection Equipment Co., Ltd., and is industrial-grade deionized water (conductivity ≤10μS / cm).

[0031] According to a preferred embodiment of the present invention, the dispersant is purchased from Jiangsu Haian Petrochemical Co., Ltd., and the model is HS-190.

[0032] According to a preferred embodiment of the present invention, the defoamer was purchased from Jiangsu Sixin Technology Application Research Institute Co., Ltd., and the model is AX-800.

[0033] According to a preferred embodiment of the present invention, the thickener is purchased from Wanhua Chemical Group Co., Ltd., and the product is [model number missing]. U300.

[0034] According to a preferred embodiment of the present invention, the leveling agent is purchased from Jiangsu Haian Petrochemical Co., Ltd., and the model is HS-333.

[0035] According to a preferred embodiment of the present invention, the titanium dioxide is purchased from Longbai Group Co., Ltd., and the model is LR-996.

[0036] According to a preferred embodiment of the present invention, the light stabilizer was purchased from Beijing Additives Research Institute and is model JGS-770.

[0037] According to a preferred embodiment of the present invention, in step A1, the reaction time is 6-8 hours after heating to 75-76°C.

[0038] According to a preferred embodiment of the present invention, in step A2, the reaction time is 4-6 hours when the temperature is lowered to 55-56°C; the reaction time is 2-4 hours when the temperature is raised to 90-92°C; the acetone washing is performed 2-3 times; and the vacuum drying temperature is 80-82°C for 12-24 hours.

[0039] According to a preferred embodiment of the present invention, the preparation method of the bio-based polyol-polysiloxane block copolymer includes: B1, dissolving soybean oil-based polyether polyol in anhydrous toluene, adding 2,4-toluene diisocyanate, and reacting under nitrogen protection at 65-66°C; B2, subsequently adding α,ω-dichloromethyl polydimethylsiloxane, and reacting at 80-82°C; finally adding dibutyltin dilaurate, reacting at 70-72°C, and distilling under reduced pressure.

[0040] This invention discloses the construction mechanism of a bio-based polyol-polysiloxane block copolymer. Multiple hydroxyl groups in a soybean oil-based polyether polyol molecule undergo nucleophilic addition reactions with the isocyanate groups of 2,4-toluene diisocyanate, forming a "polyether polyol-polyurethane" prepolymer. During this process, nitrogen protection isolates moisture from side reactions with the isocyanate (such as the formation of urea compounds), ensuring the purity of the polyurethane segments. The subsequently added α,ω-dichloromethyl polydimethylsiloxane contains a chloromethyl (-CH2Cl) functional group. The electron-withdrawing property of its chlorine atom makes the carbon atom electrophilic, easily attacked by the nucleophilic hydroxyl (-OH) at the end of the polyurethane segment, resulting in a nucleophilic substitution reaction: the oxygen atom of the hydroxyl group attacks the carbon atom of the chloromethyl group, and the chlorine atom is removed as hydrogen chloride, forming an ether bond (-O-CH2-), thereby connecting the polysiloxane segment to the polyurethane backbone, forming a "bio-based polyol-polyurethane-polysiloxane" block structure. Dibutyltin dilaurate acts as a catalyst, reducing the activation energy of the reaction through coordination and accelerating the reaction process between chloromethyl and hydroxyl groups, ultimately forming a stable block copolymer.

[0041] According to a preferred embodiment of the present invention, the soybean oil-based polyether polyol was purchased from Zhejiang Hengxiang Chemical Co., Ltd., and the model is PGE-1000 (hydroxyl value 110mgKOH / g).

[0042] According to a preferred embodiment of the present invention, the toluene was purchased from Sinopec Shanghai Petrochemical Co., Ltd., and was industrial grade toluene (purity ≥99.5%).

[0043] According to a preferred embodiment of the present invention, the 2,4-toluene diisocyanate was purchased from Wanhua Chemical Group Co., Ltd., and the product name was TDI-80 (2,4-isomer content ≥98%).

[0044] According to a preferred embodiment of the present invention, the α,ω-dichloromethyl polydimethylsiloxane was purchased from Bluestar Organosilicon (Shanghai) Co., Ltd., and the model is D-42 (chlorine content 1.8-2.2%).

[0045] According to a preferred embodiment of the present invention, the dibutyltin dilaurate was purchased from Jiangsu Sixin Technology Application Research Institute Co., Ltd., and the model is DBTDL-200 (tin content 18-20%).

[0046] According to a preferred embodiment of the present invention, the high-speed disperser was purchased from Shanghai Rut Electromechanical Equipment Co., Ltd., model RT-3000 (power 30kW, speed range 0-3000rpm).

[0047] According to a preferred embodiment of the present invention, in step B1, the reaction time is 5-10 hours after the temperature is raised to 65-66°C.

[0048] According to a preferred embodiment of the present invention, in step B2, the reaction time is 3-6 hours when the temperature is raised to 80-82°C, and 1-2 hours when the temperature is raised to 70-72°C.

[0049] This invention also provides a method for preparing the aforementioned nano-silicon environmentally friendly water-based floor coating, comprising the following steps:

[0050] S1. Add waterborne epoxy resin, borate-urethane modified polysiloxane, bio-based polyol-polysiloxane block copolymer, and deionized water sequentially to a high-speed disperser and stir to mix.

[0051] S2. Then add nano-silica sol and disperse at high speed; add titanium dioxide and dispersant, and continue dispersing;

[0052] S3. Add defoamer, leveling agent, and thickener, and stir; add light stabilizer, stir, and filter.

[0053] In this invention, the performance enhancement mechanism is achieved through the synergistic effect of multiple components. The borate ester groups in the modified compound undergo a condensation reaction with the silanol groups (-Si-OH) on the surface of nano-silicon, generating Si-OB covalent bonds. This ensures the uniform dispersion of nano-silicon in the resin matrix, preventing agglomeration. Simultaneously, the high surface energy of this group imparts superhydrophobicity to the coating, reducing stain adhesion. The polyurethane segments (flexible) and polysiloxane segments (rigid) in the bio-based polyol-polysiloxane block copolymer synergistically enhance coating hardness (wear resistance) and flexibility (impact mitigation) through dynamic hydrogen bonding. The small particle size of the nano-silica sol fills the coating pores, forming a dense structure and further reducing water permeability. The waterborne epoxy resin, as the film-forming host, forms a three-dimensional network through cross-linking, tightly binding the components. The light stabilizer absorbs ultraviolet energy and converts it into heat, delaying resin aging. Dispersants, defoamers, and other additives optimize the system uniformity, ultimately giving the floor coating high adhesion, weather resistance, wear resistance, and environmental friendliness.

[0054] According to a preferred embodiment of the present invention, in step S1, the low-speed stirring speed is 650-700 rpm and the time is 3-5 min.

[0055] According to a preferred embodiment of the present invention, in step S2, the high-speed dispersion speed is 1600-1800 rpm, the high-speed dispersion time is 25-30 min, and the dispersion time is 40-60 min.

[0056] According to a preferred embodiment of the present invention, in step S3, the stirring speed is 950-1000 rpm and the stirring time is 18-20 min; when adding the light stabilizer, the stirring speed is 550-600 rpm and the stirring time is 5-10 min; and the sieve mesh size for filtration is 180-185 mesh.

[0057] The beneficial effects of this invention are as follows:

[0058] Traditional water-based floor coatings often suffer from insufficient adhesion, easy wear, and poor weather resistance, affecting their long-term performance. This invention effectively solves these problems through the synergistic effect of two novel modified compounds. The special structure of the borate-urethane modified polysiloxane can form a strong bond with the silanol groups on the surface of nano-silicon, inhibiting nanoparticle aggregation and enhancing the adhesion between the coating and the substrate, making the coating less prone to peeling. The bio-based polyol-polysiloxane block copolymer balances hardness and flexibility, maintaining the high hardness of nano-silicon to resist daily wear, while the flexible segments alleviate impact stress and reduce the risk of cracking. The small particle size of the nano-silicon uniformly fills the pores of the coating, forming a dense structure, further improving wear resistance and extending the service life of the floor.

[0059] Environmental friendliness is one of the core advantages of this invention. Using water as the dispersion medium instead of traditional organic solvents reduces the release of volatile organic compounds (VOCs) at the source, meeting stringent environmental regulations and ensuring the health and safety of construction workers and the environment. The modified compound design does not introduce harmful chemicals, resulting in an extremely low VOC content that meets green coating standards. Simultaneously, the coating's water resistance and stain resistance are significantly improved; it does not easily absorb water and swell in humid environments, everyday stains are difficult to adhere to, cleaning and maintenance are simpler, and the environmental burden during use is reduced, aligning with the needs of sustainable development.

[0060] In practical applications, the floor coating of this invention exhibits excellent comprehensive performance and is suitable for a variety of complex scenarios. High-traffic industrial plant floors maintain high gloss and integrity even after long-term use, with no obvious signs of wear. The superior weather resistance of commercial floors prevents chalking and discoloration under ultraviolet radiation and rain, preserving their aesthetic appeal over time. Strong adhesion between the coating and the substrate ensures it is not easily peeled off in humid or temperature-sensitive environments, while its impact resistance can withstand accidental collisions or drops of heavy objects, reducing maintenance frequency. These synergistic improvements in performance not only meet high-standard usage requirements but also provide a reliable solution for floor protection in various industries. Detailed Implementation

[0061] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.

[0062] Example 1

[0063] Under nitrogen protection, 100g of α,ω-dihydroxypolydimethylsiloxane was added to a beaker, followed by 500mL of anhydrous xylene. The mixture was stirred with a glass rod until completely dissolved, forming a transparent solution. 40g of 1,6-hexamethylene diisocyanate was added to the solution, and a magnetic stirrer was turned on (200 rpm). The temperature was slowly increased to 75.5℃ (0.5℃ per minute) and maintained at this temperature for 7 hours (the temperature was recorded every 30 minutes to ensure fluctuations were ≤1℃). After the reaction was complete, the temperature was lowered to 55.5℃ (0.3℃ per minute), and 30g of polycaprolactone diol was added. The mixture was stirred for another 5 hours (150 rpm). Then, 15g of boric acid was added, and the temperature was increased to 91℃ (0.4℃ per minute). The mixture was refluxed for 3 hours (25℃ cooling water was passed through the condenser at a reflux rate of approximately 1 drop / second). After the reaction was complete, the solution was transferred to a rotary evaporator (vacuum -0.09 MPa, temperature 60℃) and distilled under reduced pressure to remove xylene and unreacted 1,6-hexamethylene diisocyanate until the distillate had no xylene odor. The product was washed twice with acetone (100 mL of acetone was added each time, stirred for 10 minutes, and allowed to stand for separation, discarding the supernatant). Finally, the washed product was transferred to a vacuum drying oven (temperature 81℃, vacuum -0.095 MPa) and dried for 18 hours to constant weight (weight change ≤0.1 g for 2 consecutive hours) to obtain borate-urethane modified polysiloxane (modified polysiloxane A), which is a colorless and transparent liquid. A small amount was taken and the hydroxyl value was measured to be 85-90 mg KOH / g.

[0064] Add 120g of soybean oil-based polyether polyol to another beaker, pour in 300mL of anhydrous toluene, and stir until completely dissolved (about 3 minutes) to form a light yellow solution. Add 50g of 2,4-toluene diisocyanate to the solution, turn on magnetic stirring (180rpm), heat to 65.5℃ (0.4℃ increase per minute), and maintain the reaction for 7 hours (record the temperature every 20 minutes, with fluctuations ≤0.8℃). After the reaction is complete, cool to 81℃ (0.5℃ increase per minute), add 80g of α,ω-dichloromethyl polydimethylsiloxane, and continue stirring for 4 hours (120rpm). Then add 2g of dibutyltin dilaurate, heat to 71℃ (0.3℃ increase per minute), and maintain the reaction for 1.5 hours (100rpm). After the reaction was complete, the solution was transferred to a rotary evaporator (vacuum degree -0.09MPa, temperature 70℃) and toluene and unreacted 2,4-toluene diisocyanate were removed by vacuum distillation until the distillate had no toluene odor, yielding a bio-based polyol-polysiloxane block copolymer (polymer B), which is a light yellow transparent liquid. A small amount was taken and the isocyanate group content was measured to be 2.5-3.0% (titrated by di-n-butylamine method).

[0065] Add 250g of waterborne epoxy resin, 60g of modified polysiloxane A, 90g of copolymer B, and 200g of deionized water to a high-speed disperser (10L capacity, 0-2000rpm). Start low-speed stirring (680rpm) for 4 minutes (observe for uniform dispersion and no clumping). Then add 250g of nano-silica sol (particle size 20-30nm, solid content 30%), increase the speed to 1700rpm (high-speed dispersion mode), and disperse for 28 minutes (observe viscosity every 5 minutes, maintaining it at 8000-9000mPa·s). Add 75g of titanium dioxide (particle size 0.5-1μm, purity ≥98%) and 9g of dispersant (anionic, solid content 40%), reduce the speed to 1500rpm, and continue dispersing for 50 minutes (check with a scraper for no particle agglomeration during this time). Add 5g of defoamer (organosilicon, 100% solids), 4g of leveling agent (acrylate, 50% solids), and 10g of thickener (associative, 25% solids). Increase the speed to 980rpm and stir for 19 minutes (observe for no layering and stable viscosity during this time). Add 8g of light stabilizer (hindered amine, 98% solids), reduce the speed to 580rpm, and stir for 7 minutes (avoid generating bubbles during this time). Finally, filter the mixture through an 180-mesh sieve (0.125mm aperture) and collect the filtrate in a clean container to obtain the nano-silicone environmentally friendly water-based floor paint. It is a uniform milky white liquid with a viscosity of 8000-9000 mPa·s at 25℃ (measured using a rotational viscometer) and a pH value of 7.5-8.0 (measured using pH test paper).

[0066] Example 2

[0067] The specific preparation method is the same as in Example 1, except that the preparation of the borate-urethane modified polysiloxane (modified polysiloxane A) is as follows: 120g of α,ω-dihydroxypolydimethylsiloxane is dissolved in 600mL of anhydrous xylene, 45g of 1,6-hexanediisocyanate is added, and the reaction is carried out at 75.8℃ for 7.5 hours; 35g of polycaprolactone diol is added, and the reaction is carried out at 55.8℃ for 5.5 hours; 18g of boric acid is added, and the reaction is carried out at 91.2℃ for 3.5 hours; the mixture is washed twice with acetone and vacuum dried at 81.5℃ for 19 hours to obtain modified polysiloxane A (hydroxyl value 88-92mgKOH / g).

[0068] Preparation of bio-based polyol-polysiloxane block copolymer (polymer B): 130g of soybean oil-based polyether polyol was dissolved in 350mL of anhydrous toluene, 55g of 2,4-toluene diisocyanate was added, and the reaction was carried out at 65.8℃ for 8 hours; 90g of α,ω-dichloromethyl polydimethylsiloxane was added, and the reaction was carried out at 81.2℃ for 4.5 hours; 2.2g of dibutyltin dilaurate was added, and the reaction was carried out at 71.2℃ for 1.8 hours; after vacuum distillation, copolymer B (isocyanate group content 2.8-3.2%) was obtained.

[0069] Preparation of Nano-Silicone Environmentally Friendly Waterborne Floor Coating: 280g of waterborne epoxy resin, 70g of modified polysiloxane A, 100g of copolymer B, and 220g of deionized water were added to a high-speed disperser and stirred at 690rpm for 4.5 minutes; 280g of nano-silica sol was added and dispersed at 1750rpm for 29 minutes; 85g of titanium dioxide and 10g of dispersant were added and dispersed for another 55 minutes; 5.5g of defoamer, 4.5g of leveling agent, and 11g of thickener were added and stirred at 990rpm for 20 minutes; 8.5g of light stabilizer was added and stirred at 590rpm for 8 minutes; the mixture was then filtered through an 180-mesh sieve to obtain the floor coating (viscosity 9000-10000mPa·s).

[0070] Example 3

[0071] The specific preparation method is the same as in Example 1, except that the preparation of the borate-urethane modified polysiloxane (modified polysiloxane A) is as follows: 80g of α,ω-dihydroxypolydimethylsiloxane is dissolved in 400mL of anhydrous xylene, 35g of 1,6-hexanediisocyanate is added, and the reaction is carried out at 75.2℃ for 6.5 hours; 25g of polycaprolactone diol is added, and the reaction is carried out at 55.2℃ for 4.5 hours; 12g of boric acid is added, and the reaction is carried out at 90.8℃ for 2.5 hours; the mixture is washed twice with acetone and vacuum dried at 80.5℃ for 17 hours to obtain modified polysiloxane A (hydroxyl value 80-85mgKOH / g).

[0072] Preparation of bio-based polyol-polysiloxane block copolymer (polymer B): 110g of soybean oil-based polyether polyol was dissolved in 280mL of anhydrous toluene, 45g of 2,4-toluene diisocyanate was added, and the reaction was carried out at 65.2℃ for 6 hours; 70g of α,ω-dichloromethyl polydimethylsiloxane was added, and the reaction was carried out at 80.5℃ for 3.5 hours; 1.8g of dibutyltin dilaurate was added, and the reaction was carried out at 70.5℃ for 1.2 hours; after vacuum distillation, copolymer B (isocyanate group content 2.2-2.6%) was obtained.

[0073] Preparation of Nano-Silicone Environmentally Friendly Waterborne Floor Coating: 220g of waterborne epoxy resin, 50g of modified polysiloxane A, 80g of copolymer B, and 180g of deionized water were added to a high-speed disperser and stirred at 660rpm for 3.5 minutes; 220g of nano-silica sol was added and dispersed at 1650rpm for 26 minutes; 65g of titanium dioxide and 8g of dispersant were added and dispersed for another 45 minutes; 4.5g of defoamer, 3.5g of leveling agent, and 9g of thickener were added and stirred at 960rpm for 17 minutes; 7.5g of light stabilizer was added and stirred at 560rpm for 6 minutes; the mixture was then filtered through an 180-mesh sieve to obtain the floor coating (viscosity 7000-8000mPa·s).

[0074] Comparative Example 1

[0075] The specific preparation method is the same as in Example 1, except that modified polysiloxane A (i.e., 250g of waterborne epoxy resin, 90g of copolymer B, 200g of deionized water, 250g of nano-silica sol, 75g of titanium dioxide, 9g of dispersant, 5g of defoamer, 4g of leveling agent, 10g of thickener, and 8g of light stabilizer) is not added, while other raw materials and process parameters remain unchanged.

[0076] Comparative Example 2

[0077] The specific preparation method is the same as in Example 1, except that copolymer B (i.e., 250g of waterborne epoxy resin, 60g of modified polysiloxane A, 200g of deionized water, 250g of nano-silica sol, 75g of titanium dioxide, 9g of dispersant, 5g of defoamer, 4g of leveling agent, 10g of thickener, and 8g of light stabilizer) is not added, while other raw materials and process parameters remain unchanged.

[0078] Comparative Example 3

[0079] The specific preparation method is the same as in Example 1, except that modified polysiloxane A and copolymer B (i.e., 250g of waterborne epoxy resin, 200g of deionized water, 250g of nano silica sol, 75g of titanium dioxide, 9g of dispersant, 5g of defoamer, 4g of leveling agent, 10g of thickener, and 8g of light stabilizer) are not added, while other raw materials and process parameters remain unchanged.

[0080] Performance testing

[0081] The floor coatings prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to the following methods:

[0082] 1. Appearance: Pour an appropriate amount of floor paint sample into a clean glass dish, let it stand at room temperature for 24 hours, and observe and record whether there is layering, sedimentation, bubbles and color uniformity (visual inspection).

[0083] 2. Viscosity: Using an NDJ-8S rotational viscometer, place the sample in a 25℃ constant temperature bath for 30 minutes to preheat, select a rotation speed of 60 rpm, immerse the rotor in the sample to the scale line, and read the viscosity value (mPa·s) after stabilizing for 1 minute.

[0084] 3. pH value: Dissolve 10g of sample in 90g of deionized water, stir well and let stand for 10 minutes. Use a wide-range pH test paper (range 1-14) to take a sample of the solution and compare it with the standard color card; or measure directly with a pH meter (model PHS-3C, accuracy 0.1).

[0085] 4. Water resistance: Apply the floor paint evenly to a 50mm×50mm×2mm glass plate (coating amount 50g / m²). 2Place the glass plate in a ventilated area to dry for 24 hours until it reaches a constant weight (m0). Completely immerse the glass plate in deionized water (the liquid level is 1 mm above the coating) and soak for 24 hours. Remove the glass plate, blot the surface moisture with filter paper, weigh the wet weight (m1), and calculate the water absorption rate = (m1-m0) / m0 × 100%.

[0086] 5. Abrasion Resistance: Using a Taber abrasion tester (model CS-10F) with a CS-10F grinding wheel (100 mesh), and a 1000g weight, the surface of a dry floor paint coating (200μm thickness) was abraded at 60rpm for 500 revolutions. After abrasion, the surface debris was removed with a brush, and the mass difference (Δm) before and after abrasion was measured using an electronic balance (accuracy 0.0001g). Abrasion amount = Δm / abrasion area (cm²) 2 ).

[0087] 6. Weather resistance: The floor paint coating (200μm thickness) was placed in a QUV ultraviolet aging chamber (model Q-LAB QUV / se) with a wavelength of 340nm (irradiance 0.77W / m). 2 The blackboard temperature was 65℃, the condensation period was 4 hours (40℃ deionized water spray), and it was removed after aging for 500 hours. The Lab values ​​before and after aging were measured using a colorimeter (model CM-700d spectrophotometer), and the color difference ΔE was calculated as √[(ΔL)]. 2 +(Δa*) 2 +(Δb*) 2 ].

[0088] 7. Hardness: Use Using a pendulum hardness tester (model KU-3), place the sample horizontally on the test platform, adjust the pendulum arm length (100mm), release the pendulum to allow it to swing freely, and record the time (in seconds) it takes for the pendulum to swing from the initial position to stop. Repeat this process 3 times and take the average value.

[0089] 8. Adhesion: Use a crisscross tool (1mm spacing, 3N blade pressure) to create a 10×10 grid on the floor coating surface. Apply 3M 600 tape (25mm width) to the grid area, then quickly peel off the tape at a 45° angle and observe the peeling. Calculate the percentage of peeling area (number of peeled grids / total number of grids × 100%).

[0090] 9. VOC content: According to GB 18582-2020 "Limits of Hazardous Substances in Building Adhesives", 50g of sample was placed in a headspace vial, sealed, and placed in a 60℃ incubator for 1 hour to equilibrate. The total VOC content (mg / kg) was calculated using gas chromatography-mass spectrometry (GC-MS, Agilent 7890B-5977A) and quantified by external standard method.

[0091] 10. Performance Test Results:

[0092] Table 1: Performance test results of each embodiment and comparative example

[0093]

[0094] As can be seen from Table 1, this invention systematically solves the problems of insufficient environmental protection, poor weather resistance, weak wear resistance, low adhesion and poor water resistance of existing water-based floor coatings through the synergistic effect of modified polysiloxane, bio-based polyol-polysiloxane block copolymer and nano silica sol. Specifically, the effects are as follows: In terms of environmental friendliness, the introduction of modified polysiloxane and block copolymer significantly reduces VOC content (VOC in the examples is only 78-92 mg / kg, far lower than 150 mg / kg in Comparative Example 1, 120 mg / kg in Comparative Example 2, and 180 mg / kg in Comparative Example 3), mainly due to the reduction of solvent evaporation and harmful monomer residues during the modification process; In terms of weather resistance, the UV shielding effect of nano-silica sol and the chemical stability of modified polysiloxane work synergistically to reduce the color difference ΔE after 500 hours of UV aging to 1.1-1.3 (ΔE in the comparative examples is 2.2-4.8), effectively inhibiting yellowing and chalking of the coating; In terms of abrasion resistance, the siloxane bonds of modified polysiloxane enhance the rigidity of the paint film, and the flexible segments of bio-based polyol-polysiloxane block copolymer improve the impact resistance of the coating. The combined effect results in an abrasion wear of only 10-14 mg / cm² at 500 revolutions. 2 (Comparative example: 18-30 mg / cm) 2 Regarding adhesion, the silanol groups of the modified polysiloxane form strong hydrogen bonds with the hydroxyl groups of the concrete substrate, and the anchoring effect of the nano-silica sol further strengthens the interfacial bonding, reducing the adhesion detachment area to 0% (comparative example 3-10%). In terms of water resistance, the long carbon chain hydrophobic groups of the modified polysiloxane and the closed structure of the nano-silica sol synergistically block water penetration, resulting in a 24-hour water absorption rate of only 0.7-0.9% (comparative example 1.5-3.2%), completely solving the problems of blistering and peeling common in traditional water-based floor coatings. In summary, through multiple mechanisms of chemical bonding, physical shielding, and interfacial strengthening, the components comprehensively improve the overall performance of the water-based floor coating.

[0095] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A nano-silicon environmentally friendly water-based floor coating, characterized in that, Including the following parts by weight of raw materials: Waterborne epoxy resin: 200-300 parts by weight; Boronate-urethane modified polysiloxane: 40-90 parts by weight; Bio-based polyol-polysiloxane block copolymer: 60-120 parts by weight; Nano silica sol: 200-300 parts by weight; Deionized water: 150-250 parts by weight; Dispersant: 7-12 parts by weight; Defoamer: 4-6 parts by weight; Thickener: 8-12 parts by weight; Leveling agent: 3-5 parts by weight; Titanium dioxide: 50-100 parts by weight; Light stabilizer: 6-10 parts by weight; The preparation method of the borate-urethane modified polysiloxane includes: A1, dissolving α,ω-dihydroxypolydimethylsiloxane in anhydrous xylene, adding 1,6-hexanediisocyanate, and reacting under nitrogen protection at 75-76℃; A2, subsequently adding polycaprolactone diol, and reacting at 55-56℃; finally adding boric acid, reacting at 90-92℃, distilling under reduced pressure, washing with acetone, and drying under vacuum.

2. The nano-silicon environmentally friendly water-based floor coating according to claim 1, characterized in that, In step A1, the temperature is raised to 75-76℃ and the reaction time is 6-8 hours.

3. The nano-silicon environmentally friendly water-based floor coating according to claim 1, characterized in that, In step A2, the reaction time is 4-6 hours when the temperature is lowered to 55-56℃; the reaction time is 2-4 hours when the temperature is raised to 90-92℃; the acetone washing is performed 2-3 times; and the vacuum drying temperature is 80-82℃ for 12-24 hours.

4. The nano-silicon environmentally friendly water-based floor coating according to claim 1, characterized in that, The preparation method of the bio-based polyol-polysiloxane block copolymer includes: B1, dissolving soybean oil-based polyether polyol in anhydrous toluene, adding 2,4-toluene diisocyanate, and reacting under nitrogen protection at 65-66℃; B2, subsequently adding α,ω-dichloromethyl polydimethylsiloxane, and reacting at 80-82℃; finally adding dibutyltin dilaurate, reacting at 70-72℃, and distilling under reduced pressure.

5. The nano-silicon environmentally friendly water-based floor coating according to claim 4, characterized in that, In step B1, the temperature is raised to 65-66℃ and the reaction time is 5-10 hours.

6. The nano-silicon environmentally friendly water-based floor coating according to claim 4, characterized in that, In step B2, the reaction time is 3-6 hours when the temperature is raised to 80-82℃; and 1-2 hours when the temperature is raised to 70-72℃.

7. A method for preparing a nano-silicon environmentally friendly water-based floor coating according to any one of claims 1-6, characterized in that, step include: S1. Add waterborne epoxy resin, borate-urethane modified polysiloxane, bio-based polyol-polysiloxane block copolymer, and deionized water sequentially to a high-speed disperser and stir to mix. S2. Then add nano-silica sol and disperse at high speed; add titanium dioxide and dispersant, and continue dispersing; S3. Add defoamer, leveling agent, and thickener, and stir; add light stabilizer, stir, and filter.

8. The preparation method according to claim 7, characterized in that, In step S1, the low-speed stirring speed is 650-700 rpm for 3-5 minutes.

9. The preparation method according to claim 7, characterized in that, In step S2, the high-speed dispersion speed is 1600-1800 rpm, the high-speed dispersion time is 25-30 min, and the continued dispersion time is 40-60 min.

10. The preparation method according to claim 7, characterized in that, In step S3, the stirring speed is 950-1000 rpm and the stirring time is 18-20 min; when adding the light stabilizer, the stirring speed is 550-600 rpm and the time is 5-10 min; the sieve mesh size is 180-185 mesh.

Citation Information

Patent Citations

  • Antistatic wear-resistant polyurethane terrace coating and preparation method thereof

    CN111662633A

  • Polysiloxane modified waterborne epoxy resin emulsion and preparation method thereof

    CN112592657A

  • Coated particles and coating compositions comprising coated particles

    US20090286901A1